ENHANCING THE TEACHING OF FUNCTIONS IN THE FET PHASE IN THE SOUTH AFRICAN CONTEXT: A CRITICAL REVIEW OF DIGITAL TOOLS AND AI-DRIVEN METHODS (Proceedings of the International Conference on Education, 2025)
This study critically reviews the integration of digital tools in the teaching of Functions within the Further Education and Training (FET) phase in high schools, in the context of the rapidly evolving, AI-driven digitalization era. The increasing influence of artificial intelligence (AI) in education, accelerated by the demands of the Fourth Industrial Revolution (4IR) presents new opportunities for transforming mathematics instruction through dynamic, interactive, and technology- enhanced pedagogies. Despite the availability of advanced digital tools such as GeoGebra, Desmos, and various mobile applications, their use in teaching the topic of Functions remains limited and inconsistently applied. Many teachers continue to face challenges in effectively leveraging these technologies to support students' conceptual understanding, thereby reducing the overall impact of digital innovation in the mathematics classroom. To address this gap, the study employs a qualitative case study approach through a systematic literature review, drawing on secondary data from academic databases such as Scopus and Web of Science. The review is framed by the SAMR model and the TPACK framework, which provide a conceptual basis for analysing how digital tools are currently being integrated and how they might be used more effectively. Descriptive and exploratory methods are applied to synthesize insights across the literature. The findings highlight the potential of digital tools and AI-enhanced strategies to improve learner engagement and conceptual mastery in the teaching of Functions. The study concludes by emphasizing the need for intentional, well-supported integration of digital technologies in mathematics education practices.
Keywords: digitalization; digital technology tools; AI methods; functions (FET phases); high school; mathematics teachers and qualitative research; SAMR and TPACK